Exploratory Factor Analysis of the Effects of Design on Brand Strategy-Performance in Malaysian Furniture Firms - Tamyez, Puteri Fadzline; Nor, Norzanah Mat; Mohamad, Syed Jamal Abdul Nasir bin Syed (Richtmann Publishing, 2012)
To investigate the performance of the Malaysian furniture companies in the context of design and brand strategy, aself-administered questionnaire survey was conducted. This research was conducted to examine the effects of design on thebrand strategy towards a better export performance among companies. It is an important strategic tool that can help firms tomanage their business activities more efficiently as well as provide them with their competitive edge, has attracted significantresearch attention. Despite the increased research attention in recent years, limited numbers of empirical studies haveinvestigated how small and medium-sized firms (SMEs) perceived design, in the Malaysian context. The subjects involved in thesurvey included 223 furniture companies participating in the Malaysian Furniture Fair (MIFF 2012) that are highly committed inexporting. Consequently, it resulted in a return of 116 questionnaires that were furthered analyzed. This study sought to addressthis research issue by examining the perceptions of owners and managers of 116 furniture SMEs concerning design and theirbranding strategy in the Malaysian furniture industry. The findings suggest favourable perceptions of design among the SMEsbrand strategy surveyed.